A telomere-to-telomere assembly of Oscheius tipulae and the evolution of rhabditid nematode chromosomes. Issue 1 (8th December 2020) - Gonzalez de la Rosa, Pablo Manuel; Thomson, Marian; Trivedi, Urmi; Tracey, Alan; Tandonnet, Sophie; Blaxter, Mark
Abstract : Here, González de la Rosa et al . explore the phylogenetic stability of nematode chromosomes using a new telomere-to-telomere assembly of the rhabditine nematode Oscheius tipulae generated from nanopore long reads. The authors resolve the 60 Mb genome into six chromosomal molecules and find evidence of specific chromatin diminution at all telomeres. They present a model for the evolution of nematode chromosomes through rearrangement and fusion of seven ancestral Nigon elements. Abstract: Eukaryotic chromosomes have phylogenetic persistence. In many taxa, each chromosome has a single functional centromere with essential roles in spindle attachment and segregation. Fusion and fission can generate chromosomes with no or multiple centromeres, leading to genome instability. Groups with holocentric chromosomes (where centromeric function is distributed along each chromosome) might be expected to show karyotypic instability. This is generally not the case, and in Caenorhabditis elegans, it has been proposed that the role of maintenance of a stable karyotype has been transferred to the meiotic pairing centers, which are found at one end of each chromosome. Here, we explore the phylogenetic stability of nematode chromosomes using a new telomere-to-telomere assembly of the rhabditine nematode Oscheius tipulae generated from nanopore long reads. The 60-Mb O. tipulae genome is resolved into six chromosomal molecules. We find the evidence of specific chromatin diminution at all telomeres. Comparing this chromosomal O. tipulae assembly with chromosomal assemblies of diverse rhabditid nematodes, we identify seven ancestral chromosomal elements (Nigon elements) and present a model for the evolution of nematode chromosomes through rearrangement and fusion of these elements. We identify frequent fusion events involving NigonX, the element associated with the rhabditid X chromosome, and thus sex chromosome-associated gene sets differ markedly between species. Despite the karyotypic stability, gene order within chromosomes defined by Nigon elements is not conserved. Our model for nematode chromosome evolution provides a platform for investigation of the tensions between local genome rearrangement and karyotypic evolution in generating extant genome architectures.